1995
DOI: 10.1021/es00004a006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Annual Water-Air Fluxes of Polychlorinated Biphenyls in Lake Michigan

Abstract: Air-water exchange of PCBs was determined in Lake Michigan on an event and seasonal basis in 1991 -1993. Instantaneous fluxes of CPCB (sum of 77 congener peaks) based on air-water concentration gradients drawn from air and water samples collected simultaneously aboard ship demonstrated net volatilization in September 1991. Air samples collected on the northeastern shore of Lake Michigan (Sleeping Bear Dunes State Park) between December 1991 and July 1993 showed no seasonal trend in vapor-phase CPCB concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
88
0
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 30 publications
12
88
0
7
Order By: Relevance
“…The fluxes of ∑PCBs in spring were depositional while they were volatilized in summer. In another study conducted in Lake Michigan in September 1991, all PCB fluxes were from water to air and they ranged from −24 to −220 ng m − 2 day − 1 (Hornbuckle et al, 1995). Totten et al (2001) have also found net volatilization for PCBs in the New York-New Jersey Harbor Estuary in July 1998 and the net flux ranged from −310 to −2700 ng m − 2 day − 1 .…”
Section: Air-water Exchangementioning
confidence: 94%
“…The fluxes of ∑PCBs in spring were depositional while they were volatilized in summer. In another study conducted in Lake Michigan in September 1991, all PCB fluxes were from water to air and they ranged from −24 to −220 ng m − 2 day − 1 (Hornbuckle et al, 1995). Totten et al (2001) have also found net volatilization for PCBs in the New York-New Jersey Harbor Estuary in July 1998 and the net flux ranged from −310 to −2700 ng m − 2 day − 1 .…”
Section: Air-water Exchangementioning
confidence: 94%
“…The 1991 and 1994 (w/o urban influence) budgets were updated to be temporally consistent with data from the AEOLOS results for 1994-95, and included new atmospheric deposition estimates (e. g., Hornbuckle et al, 1995;Hoff et al, 1996;Hillery et al, 1998).…”
Section: Pcb Mass Budget In Lake Michigan With and Without The Inflmentioning
confidence: 99%
“…The atmosphere serves as an important pathway for global transport of PCBs. Particle deposition (Zannetti, 1990;Noll et al, 1990), gaseous air-water exchange (Hornbuckle et al, , 1995Jeremiason et al, 1994;Zhang et al, 1999) and wet deposition via rain and snow (Franz 1994;Poster and Baker, 1996) are the major atmospheric removal mechanisms for PCBs.…”
Section: Introductionmentioning
confidence: 99%
“…Murphy et al (1981) employed filters that were wetted with propane and butanediols as a collection surface. PCBs enter the atmosphere from incinerators, landfills, or soil and air/water exchange (Murphy et al, 1981(Murphy et al, , 1985Hornbuckle et al, 1994Hornbuckle et al, , 1995Jeremiason et al, 1994;Zhang et al, 1999;Franz, 1994;Poster and Baker, 1996;Hsu et al, 2003;Garcia-Alonso and Perez-Pastor, 2003). Since there are some important PCB sources around Chicago, the atmospheric concentrations of PCBs are higher there than many other urban areas (Tasdemir et al, 2004;Green et al, 2000;Simcik et al, 1998;Cotham and Bidleman, 1995).…”
mentioning
confidence: 99%